Successful nonoperative management in Grade-V multiorgan injury of the spleen, liver, and kidney: A case report - Aldwin Tanuwijaya; Kshetra Rinaldhy; Rizky Amaliah (Elsevier, 2024)
Introduction: Nonoperative management (NOM) which includes bed rest, routine monitoring, and blood transfusions if needed, is recommended for all stable patients with single organ injury due to blunt trauma, regardless of the severity of the injury. However, limited guidelines and studies have addressed NOM for multiorgan injuries in children, especially in high-grade (AAST grade IV/V) injuries. Case presentation: A 16-year-old male was referred to our hospital after being involved in a single motorcycle accident. Vital signs were within normal limits. Physical examination revealed visible abrasions on the left chest, and tenderness on palpation of the entire abdomen, especially in the upper right and left. Laboratory findings revealed Hb 9.3 g/dL, leucocytosis 43,850, AST 201 U/L, and ALT 237 U/L. CT-Scan revealed an AAST Grade-V spleen injury, an AAST Grade-V left kidney injury, an AAST grade II liver injury, fractures of the 6th and 7th left ribs, and a left hemothorax. The management consisted of bedrest, serial monitoring, and transfusion of packed red cells and fresh frozen plasma for a hemoglobin level of 7.9 mg/dl. A chest tube was placed in the left hemithorax. The patient gradually recovered well and was discharged 16 days after the admission. He was advised to only engage in minimal activities at home. Four months after the injury a follow-up abdominal CT scan revealed a small peri-splenic cyst and a small left kidney. Renogram found that the GFR of the left kidney was reduced, but no further management was required. Conclusion: NOM guidelines used for high-grade single-organ injuries could be applicable to high-grade multi-organ injuries.